Extended-spectrum beta-lactamases in ceftazidime-resistant Escherichia coli and Klebsiella pneumoniae isolates in Turkish hospitals - Hoşo?lu, S.; Gundes, S.; Kolayli, F.; Karadenizli, A.; Demirda?, K.; Gunaydin, M.; Ucmak, H. (Medknow Publications and Media Pvt. Ltd, 2007)
Purpose: To study the prevalence of TEM-, SHV- and GES-type ?-lactamases among Escherichia coli and Klebsiella pneumoniae strains having ceftazidime MICs higher than 2 mg/L. Methods: A total of 63 E. coli and 41 K. pneumoniae isolated from five different university hospitals were studied for the existence of TEM-, SHV- and GES-type ?-lactamases. Susceptibility tests were carried out according to the criteria of National Committee for Clinical Laboratory Standards. MICs were obtained by agar dilution method. Existence of extended-spectrum ?-lactamases (ESBLs) were assessed by double-disc synergy test (DDST). Existence of the above-mentioned ?-lactamase genes were studied both by PCR with specific oligonucleotide primers and isoelectric focusing methods. Results: None of the isolates were carbapenem-resistant. DDSTs were positive in 50 (79.3%) and 33 (80.5%) of E. coli and K. pneumoniae , respectively. TEM gene was detected in 41 (65.1%) and 19 (46.3%), whereas SHV gene in 18 (28.6%) and 20 (48.8%) of E. coli and K. pneumoniae strains, respectively. GES genes were not detected. Conclusions: TEM and SHV genes are highly prevalent among ESBL-producing E. coli and K. pneumoniae , whereas GES-type ESBLs are absent and found not to be responsible of ceftazidime resistance in Turkish hospitals.
Keywords: Ceftazidime-resistant; E. coli; ESBL; GES; Klebsiella; SHV; TEM